Research on Fatigue Model of Semi-Rigid Base Asphalt Pavement before and after Polymer Grouting - Bei Zhang; Xu Zhang; Yanhui Zhong; Xiaolong Li; Meimei Hao; Xianwei Sang; Xiaoliang Wang; Jianyang Liu (Advances in Civil Engineering)
To improve the service life of a semirigid base asphalt pavement and prolong its service cycle, it is imperative to conduct long-term performance research before and after pavement disease repair. This study proposes a fatigue damage model for pavement and polymer materials and uses the finite element method to establish a three-dimensional numerical model of a semirigid base asphalt pavement structure. Moreover, it compares and analyzes the mechanical response and fatigue damage of this pavement before and after polymer repair. The evolution law is verified by indoor fatigue tests. The results show that, under a standard load of 0.7 MPa, the vertical displacement and the Mises stress of the vacant position after the polymer repair are reduced by 61% and 69%, respectively. Under a cyclic load of 1.2 MPa, the number of load actions increases from 500,000 to more than 5 million, and the fatigue damage factor of the polymer is reduced by 29%. With the increase in the number of fatigue test loads, the cumulative evolution trend of the fatigue damage is basically consistent with the results of the numerical simulation, which verifies the rationality of the numerical model. This research is relevant for providing a reference for extending the service life of expressways and improving the technical level of expressway maintenance.